2022
DOI: 10.1177/08445621221113734
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum, Theory, and Practice: Exploring Nurses’ and Nursing Students’ Knowledge of and Attitudes towards Caring for the Older Adults in Canada

Abstract: Background Caring for older adults is among the most challenging issue of public health and social care systems in modern societies. By enhancing the nursing curriculum, nursing students will be qualified to provide gerontology care, and they will be acknowledging and working to eliminate ageism from the health care system. Purpose This study explores nurses’ and nursing students’ knowledge and attitudes in caring for older adults and addresses the factors contributing to nurses’ perspectives. It also examines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Similar findings showed that attitudes and knowledge about aging had substantial positive regression weights, suggesting that nursing students with higher scores for these variables would be anticipated to be more receptive to working with senior citizens. 57 Another similar study finding shows that there is significant positive correlation between nurses' attitudes and knowledge level. These might be similar socio-demographic variables of the respondents.…”
Section: Discussionmentioning
confidence: 81%
“…Similar findings showed that attitudes and knowledge about aging had substantial positive regression weights, suggesting that nursing students with higher scores for these variables would be anticipated to be more receptive to working with senior citizens. 57 Another similar study finding shows that there is significant positive correlation between nurses' attitudes and knowledge level. These might be similar socio-demographic variables of the respondents.…”
Section: Discussionmentioning
confidence: 81%
“…For instance, most Canadian nurses and nursing students have been found to have an average level of knowledge, which causes them to have a neutral attitude toward their elderly patients. As the nursing curriculum should have a positive impact on the attitude, knowledge and skills of the majority of student nurses, it seems there is a need for an elderly nursing curriculum to improve nursing students' human caring, knowledge and skills in this area (Mohamed & DeCoito, 2023). In the design of teaching and learning based on practice and curriculum research community, the results of developing activities to enhance teaching potential reveal four components: principles, activity objectives, learning activities, and learning evaluation (Cojorn & Sonsupap, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with those of studies conducted in Korea, 25 Egypt, 23 and Canada. 30 In general, knowledge and competence are closely related since providing care for geriatric patients involves understanding the difficulties they face as well as complicated intervention techniques. 31 This is due to the fact that those who have good knowledge about the care of older patients understand more about the problems of older people, which might in turn enhance their skills.…”
mentioning
confidence: 99%